2016
DOI: 10.1016/j.pnpbp.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical needs in drug discovery for cessation of alcohol and nicotine polysubstance abuse

Abstract: Polysubstance abuse of alcohol and nicotine has been overlooked in our understanding of the neurobiology of addiction and especially in the development of novel therapeutics for its treatment. Estimates show that as many as 92% of people with alcohol use disorders also smoke tobacco. The health risks associated with both excessive alcohol consumption and tobacco smoking create an urgent biomedical need for the discovery of effective cessation treatments, as opposed to current approaches that attempt to indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 389 publications
(484 reference statements)
0
26
0
Order By: Relevance
“…; Tizabi et al , ; Truitt et al ). Multiple reports have indicated that naltrexone and varenicline, the pharmacological ‘gold standards’ for treating AUD and nicotine dependence, both fail to alter the concurrent co‐administration of EtOH+NIC (Van Skike et al ; Waeiss, Knight, Hauser et al ; Maggio et al ). The current results provide clear preclinical data indicating that EtOH+NIC co‐administration results in a unique neurological cascade that is not observed following comparable exposure to EtOH or NIC alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Tizabi et al , ; Truitt et al ). Multiple reports have indicated that naltrexone and varenicline, the pharmacological ‘gold standards’ for treating AUD and nicotine dependence, both fail to alter the concurrent co‐administration of EtOH+NIC (Van Skike et al ; Waeiss, Knight, Hauser et al ; Maggio et al ). The current results provide clear preclinical data indicating that EtOH+NIC co‐administration results in a unique neurological cascade that is not observed following comparable exposure to EtOH or NIC alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to examine the shared neurobiological mechanisms and subsequent effects on behavior by concurrent EtOH and NIC exposure, rather than individually. A growing body of research suggests the interactions between EtOH and NIC may stem from direct and indirect modulation of the mesocorticolimbic pathway as well as dysregulation of neurotransmitter regulatory systems (Van Skike et al ). Previous research from our laboratory has demonstrated EtOH and NIC co‐exposure consistently results in unique alterations to the mesocorticolimbic pathway that is not evident with either drug alone.…”
mentioning
confidence: 99%
“…Alcohol and tobacco use is the most common form of polysubstance use and remains a significant clinical challenge [ 135 ]. For example, within a large, representative survey of adults in the U.S., higher levels of cigarette smoking and nicotine dependence were found in those who drank more alcohol or met criteria for an alcohol use disorder [ 136 ].…”
Section: E-liquid Components and Characteristicsmentioning
confidence: 99%
“…For example, escalation of drinking following nicotine exposure is associated with a nicotine‐driven blunting of alcohol‐induced dopamine release in the ventral striatum (Doyon et al., ). There is now a growing interest in mechanisms associated with nicotine and alcohol interactions, although information on behavioral and neuronal signaling adaptations that occur in animals exposed to both nicotine and alcohol remains limited compared to the abundance of studies on these substances in isolation (Van Skike et al., ).…”
mentioning
confidence: 99%